Low dose oral hydroxyurea prophylaxis improves all clinico: haematological parameters among sickle cell disease patients - Pradhan, Butungeshwar; Kullu, Bipin K.; Tripathy, Sagnika; Patel, Nayan K. (International Journal of Research in Medical Sciences, 2018)
Background: Sickle cell disease (SCD) an inheritable disorder of haemoglobin structure resulting from substitution of valine for glutamic acid at 6th position of β-globin chain of haemoglobin(HbS), which polymerizes on deoxygenation and undergoes to sickle shaped RBC causing vaso-occlusive painful crisis, chronic haemolysis, anaemia, frequent blood transfusions, frequent hospitalizations with increased morbidity and acute chest syndrome leading to mortalities. Presence of foetal haemoglobin (HbF) prevent sickling and use of drugs like Hydroxyurea (HU) results in increased production of HbF to prevent complications of SCD. Aims and objectives was to know the various effect of low dose HU on clinical and haematological parameters among SCD patients. Methods: Total 100 S HbSS patients were consecutively selected, with indication for HU in 10mg/kg + 5mg folic acid/day. Baseline haemoglobin, HbF, HbS, haematocrit (HCT), TRBC, MCV, MCH, MCHC, and HbS, TPC, TWBCs, ANCs and other relevant tests as needed. Follow up haematological tests were done at 1 month and then every 3 month up to 24 months with monitoring of clinical status, hepatic, renal, and myelotoxicities. Data were collected and analyzed. Results: There were 31 paediatric cases with mean age of 8.47±4.1 years and 69 adults with mean age of 25.9±8.2 years presented with or history of various complications. HU improves all clinical and haematological parameters significantly (Hb, HCT, HbF, MCV, MCH, MCHC,) with mild myelotoxicities (decreased ANC, TPC, WBCs). Conclusions: HU improves all clinical and haematological parameters with mild myelotoxicities among SCD patients.